Empowering Micro Entrepreneurs through AI Based Digital Financial Management Mentoring in Kurungan Nyawa Village, Pesawaran Regency - Tokit Masditok; Sastya Putri; Eko Aziz Apriadi (CV. Tripe Konsultan, 2026)
This community service program aimed to empower 30 micro-entrepreneurs in Kurungan Nyawa Village, Pesawaran Regency, through Artificial Intelligence (AI)-based digital financial management assistance. The program integrated financial separation, digital transaction recording, cash-flow analysis, simple budgeting, AI prompt construction, and AI-output verification using a participatory mentoring approach. Activities included baseline assessment, workshops, guided practice, individual clinics, and follow-up monitoring. The results showed that overall competency increased from 1.63 before assistance to 3.30 after assistance, with a gain of 1.67 points. The highest post-assistance score was achieved in digital transaction recording (3.53), while the greatest improvement occurred in AI prompt construction (+1.84). AI-output verification also increased from 1.30 to 3.10. These findings indicate that the record–prompt–verify–decide model effectively strengthened financial-management competence and encouraged responsible AI use, with AI positioned as a decision-support tool under human verification and judgement.